2001
DOI: 10.1021/la0010222
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Confined Monomers on Electrode Surfaces. 11. Electrochemical and Infrared Spectroscopic Characteristics of Aniline-Terminated Alkanethiol Monolayers on Au Electrochemically Treated in Nonaqueous Media

Abstract: The stability and electrochemical properties in nonaqueous media of self-assembled alkanethiol monolayers containing an alkoxyaniline tail group tethered to a gold surface via a hexyl or heptyl chain were investigated. It was previously found that upon electrochemical oxidation in 1 M H2SO4, 2-(6-mercaptohexan-1-oxy)aniline (AnC6SH) and 2-(7-mercaptoheptan-1-oxy)aniline (AnC7SH) monolayers on Au give rise to surface-confined dimeric and oligomeric/polymeric anilines as well as surface-confined hydrolyzed anili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…The CV clearly shows oxidation and reduction peaks at +0.65 and +0.52 V (vs Ag/AgCl), respectively. The observed electrochemical behavior is quite similar to that obtained during the polymerization of aniline and ring-substituted anilines dissolved in acidic solutions. , The large currents observed at the maximum positive potential are due to the superposition of two distinct processes: one is electron transfer from poly(NDDEAEA), corresponding to the oxidation of the PANI film, and the other is electron transfer from the monomer, NDDEAEA, to the electrode, corresponding to the oxidation of NDDEAEA to produce a precursor of polyaniline formation. In order to investigate the stability of poly(NDDEAEA) films, the electropolymerized electrodes were dipped into a solution of HCl (0.75 M), and the CV was measured.…”
Section: Resultssupporting
confidence: 67%
“…The CV clearly shows oxidation and reduction peaks at +0.65 and +0.52 V (vs Ag/AgCl), respectively. The observed electrochemical behavior is quite similar to that obtained during the polymerization of aniline and ring-substituted anilines dissolved in acidic solutions. , The large currents observed at the maximum positive potential are due to the superposition of two distinct processes: one is electron transfer from poly(NDDEAEA), corresponding to the oxidation of the PANI film, and the other is electron transfer from the monomer, NDDEAEA, to the electrode, corresponding to the oxidation of NDDEAEA to produce a precursor of polyaniline formation. In order to investigate the stability of poly(NDDEAEA) films, the electropolymerized electrodes were dipped into a solution of HCl (0.75 M), and the CV was measured.…”
Section: Resultssupporting
confidence: 67%
“…Furthermore, they have shown that the electrochemical oxidation of 4-ATP at pH ≥ 6 does not yield the redox species giving a reversible redox response, which is distinct from the case of an acidic solution, probably due to the formation of electroinactive products . During the course of the present investigation, two reports appeared discussing the electrochemical oxidation of aniline-terminated alkanethiol monolayers in aqueous acidic and nonaqueous media . According to these reports, the electrochemical oxidation of an aniline-terminated alkanethiol monolayer results in the formation of polymer, dimer, and hydrolyzed dimer …”
Section: Introductionmentioning
confidence: 74%
“…During the course of the present investigation, two reports appeared discussing the electrochemical oxidation of aniline-terminated alkanethiol monolayers in aqueous acidic and nonaqueous media . According to these reports, the electrochemical oxidation of an aniline-terminated alkanethiol monolayer results in the formation of polymer, dimer, and hydrolyzed dimer …”
Section: Introductionmentioning
confidence: 97%
“…It has been demonstrated with a variety of systems that surface-confined monomers of conductive polymers can serve as nucleation sites for the chemical or electrochemical growth of conductive polymer films. Particular systems investigated include SAMs capped with pyrrole, [14][15][16][17][18][19][20][21][22] aniline, [23][24][25] and thiophene [26][27][28][29][30] monomers, with most of these studies having been done on silicon or gold substrates. The involvement of the surface-confined monomer units in the polymerization results in a strongly adhered, conductive polymer layer compared to what is achieved by electropolymerization from bulk solution onto an unmodified surface.…”
Section: Introductionmentioning
confidence: 99%